Pentingnya Pemahaman tentang Jajanan Sehat pada Anak di Taman Kanak-Kanak Baiturrahim Jambi - Iin Indrawati; Faridah Faridah (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
The main factor that most influences the normal development of children under five is the intake of food in good quantity and quality. This is very beneficial for the process of growth and development as well as maintaining health in the prevention of several diseases or health problems. Healthy food should be given by the mother to the children for whom she is responsible. Important knowledge about healthy food and its benefits must be clearly known and understood by parents, especially mothers. However, currently there is a lot of information that can provide knowledge about the importance of nutrition that can be accepted and can even be sought by parents who come from social media. Parents who have good knowledge will be able to provide good food to their children.Baiturrahim Kindergarten (TK) is one of the kindergartens that has been around for a long time, since its establishment in 1992 Baiturrahim Kindergarten always has around 50 students every year, so this community service activity is directed to be carried out at Baiturrahim Kindergarten . It is estimated that the implementation time for all activity processes will be completed in a period of 6 months starting from September 2019 to February 2020